Measurement of the inclusive 3-jet production differential cross section in proton-proton collisions at 7 TeV and determination of the strong coupling constant in the TeV range - (:unkn) unknown (SPRINGER, 2015)
This paper presents a measurement of the inclusive 3-jet production differential cross section at a proton-proton centre-of-mass energy of 7 TeV using data corresponding to an integrated luminosity of 5 fb(-1) collected with the CMS detector. The analysis is based on the three jets with the highest transverse momenta. The cross section is measured as a function of the invariant mass of the three jets in a range of 445-3270 GeV and in two bins of the maximum rapidity of the jets up to a value of 2. A comparison between the measurement and the prediction from perturbative QCD at next-to-leading order is performed. Within uncertainties, data and theory are in agreement. The sensitivity of the observable to the strong coupling constant alpha(S) is studied. A fit to all data points with 3-jet masses larger than 664 GeV gives a value of the strong coupling constant of alpha(S)(M-Z) = 0.1171 +/- 0.0013 (exp) (+0.0073)(-0.0047) (theo).
Keywords: PARTON DISTRIBUTIONS; MODEL; FRAGMENTATION